Kerosene Intoxication in Dr. Pirngadi Hospital Medan, Indonesia - Arman Panjaitan; Endang D. Hamid; Dachrul Ardi; Zakaria Siregar (Indonesian Pediatric Society, 1984)
A retrospective study on kerosene intoxication in children was conducted in Dr. Pirngadi Hospital Medan during the period 1976- 1981. In this period 13504 children were hospitalized of which 144 cases ( 1. 66%) were with kerosene intoxication. Age peak incidence was 1- 3 years (75.69%), of whom 66.66% were boys. Male to female ratio was 96 to 48 ( 2 : 1 ). The majority of cases were brought to the hospital in less than one hour after ingestion of kerosene. The major presenting symptoms were coughing (45.83%, vomiting (40.28%, dyspnea (25.65%, bronchopneumonia (15.97%) and restlessness (7.59%. Mortality was 5.55%. Careless storage was the main cause of kerosene intoxication.